Material hardship, prefrontal cortex–amygdala structure, and internalizing symptoms in children. Issue 2 (4th August 2020) - Lichtin, Rebecca D.; Merz, Emily C.; He, Xiaofu; Desai, Pooja M.; Simon, Katrina R.; Melvin, Samantha A.; Maskus, Elaine A.; Noble, Kimberly G.
Abstract: Material hardship, or difficulty affording basic resources such as food, housing, utilities, and health care, increases children's risk for internalizing problems. The uncinate fasciculus (UNC) and two of the gray matter regions it connects—the orbitofrontal cortex (OFC) and amygdala—may play important roles in the neural mechanisms underlying these associations. We investigated associations among material hardship, UNC microstructure, OFC and amygdala structure, and internalizing symptoms in children. Participants were 5–9‐year‐old children ( N  = 94, 61% female) from socioeconomically diverse families. Parents completed questionnaires assessing material hardship and children's internalizing symptoms. High‐resolution, T1‐weighted magnetic resonance imaging ( n  = 51), and diffusion tensor imaging ( n  = 58) data were acquired. UNC fractional anisotropy (FA), medial OFC surface area, and amygdala gray matter volume were extracted. Greater material hardship was significantly associated with lower UNC FA, smaller amygdala volume, and higher internalizing symptoms in children, after controlling for age, sex, and family income‐to‐needs ratio. Lower UNC FA significantly mediated the association between material hardship and internalizing symptoms in girls but not boys. These findings are consistent with the notion that material hardship may lead to altered white matter microstructure and gray matter structure in neural networks critical to emotion processing and regulation.